Architectures for Microgrids Interconnection - Chavez-Orostica, H (IEEE, 2020)
Progress requires greater global energy interconnection. This paper presents an overview of the topologies and control techniques applied to microgrids, by means of an updated bibliographic research and the most relevant articles on the use of power electronics in microgrids interconnection. The topologies and control techniques investigated in this paper expose a reality that leads to commercial solutions applied to microgrids, giving new tools to the energy market.